2019
DOI: 10.1182/blood-2019-129175
|View full text |Cite
|
Sign up to set email alerts
|

GRK6 Regulates the Hemostatic Response to Injury through Its Rate-Limiting Effects on GPCR Signaling in Platelets

Abstract: Inappropriate platelet activation remains a major cause of cardiovascular and cerebrovascular diseases. Most agonists activate platelets through G protein-coupled receptors (GPCRs). However, questions remain about mechanisms that provide negative feedback towards activated GPCRs to limit platelet activation and thrombus formation. Here we provide the first evidence that GPCR kinase 6 (GRK6) serves this role in platelets, using GRK6-/- mice generated by CRISPR-Cas9 genome editing to examine the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…Messenger RNA and predicted protein copy number analysis in human and mouse platelets have identified the presence of GRK expression [ 21 , 22 , 23 ]. Further study using immunoblotting has confirmed the expression of specific GRKs (GRK2, GRK5, and GRK6) in platelets [ 24 , 25 , 26 ]. In human platelets, GRK2, GRK5, and GRK6 are all expressed in the range of 1000–2000 copies per platelet, with GRK6 having the highest expression level.…”
Section: Grks In Plateletsmentioning
confidence: 97%
See 4 more Smart Citations
“…Messenger RNA and predicted protein copy number analysis in human and mouse platelets have identified the presence of GRK expression [ 21 , 22 , 23 ]. Further study using immunoblotting has confirmed the expression of specific GRKs (GRK2, GRK5, and GRK6) in platelets [ 24 , 25 , 26 ]. In human platelets, GRK2, GRK5, and GRK6 are all expressed in the range of 1000–2000 copies per platelet, with GRK6 having the highest expression level.…”
Section: Grks In Plateletsmentioning
confidence: 97%
“…In both human and mouse platelets, GRK6 is the predominant form of GRKs. It impacts platelet activation through targeting of the PARs and P2Y 12 receptors ( Figure 1 A) [ 25 ]. Human platelets express thrombin receptors, PAR1 and PAR4, but mouse platelets express a PAR3/PAR4 complex [ 37 , 38 ].…”
Section: The Role Of Grks and Arrestins During Platelet Activationmentioning
confidence: 99%
See 3 more Smart Citations